Optimisation of wet pressure drop in nonwoven fibrous, knitted, and open-cell foam filters - Golkarfard, V.; King, Andrew; Sridhar, Abishek; Mead-Hunter, Ryan; Kasper, G.; Mullins, B. (Pergamon Press, 2019)
This work investigates the relationship between wet (multi-phase) pressure drop, saturation and filter face velocity in mist (or coalescing) filters in order to evaluate optimum operating conditions. Three different structural types of oleophobic filter media (fibrous, knitted and open-cell foam), with equivalent clean filtration efficiency and pressure drop, were investigated numerically over a wide range of inlet velocities (0.05–2 m·s-1). The numerical results indicate the balance between saturation/flow resistance and pressure drop of the filter media with increasing velocity. Experiments were also conducted to validate the trends found in simulations. Both the numerical and experimental results show a local optimum in the pressure drop profile, due to flow regime transition. This effect has not previously been documented due to a lack of parametric studies in this region. This region may be an optimal operating regime for some applications.